The United States of Europe European Union and the Euro Revolution - Dutta, Manoranjan (Contributions to economic analysis ;, 2012)
The United States of Europe considers the post-WWII transition of Europe from a diverse and disparate continent to the economically integrated European Union of today. Initiated by the Benelux Customs Union, and later the European Coal and Steel Cooperation, the six-member European Economic Community was formed in 1957, becoming the EC in 1967, and finally the EU in 1992. This process of Europeanization reached its zenith in 1987 with the approval of the Single European act, creating a single market economy. This was followed in 1993 by the Maastricht Treaty, defining the intra-EU macro- and micro-economic parameters. The inauguration of a single common currency, the euro, on 1st January 1999 was a further innovative step, a process that has enabled the EU-27 to enjoy a competitive share of the world GDP and trade.